Plasma 25-Hydroxyvitamin D Concentrations Are Inversely Associated with All-Cause Mortality among a Prospective Cohort of Chinese Adults Aged ≥80 Years. Issue 6 (5th April 2019) - Mao, Chen; Li, Fu-Rong; Yin, Zhao-Xue; Lv, Yue-Bin; Luo, Jie-Si; Yuan, Jin-Qiu; Mhungu, Florence; Wang, Jiao-Nan; Shi, Wan-Ying; Zhou, Jin-Hui; Chen, Guo-Chong; Gao, Xiang; et al.
ABSTRACT: Background: High concentrations of plasma 25-hydroxyvitamin D [25(OH)D], a marker of circulating vitamin D, have been associated with a lower risk of mortality in epidemiologic studies of multiple populations, but the association for Chinese adults aged ≥80 y (oldest old) remains unclear. Objective: We investigated the association between plasma [25(OH)D] concentration and all-cause mortality among Chinese adults aged ≥80 y. Design: The present study is a prospective cohort study of 2185 Chinese older adults (median age: 93 y). Prospective all-cause mortality data were analyzed for survival in relation to plasma 25(OH)D using Cox proportional hazards regression models, with adjustments for potential sociodemographic and lifestyle confounders and biomarkers. The associations were measured with HR and 95% CIs. Results: The median plasma 25(OH)D concentration was 34.4 nmol/L at baseline. Over the 5466 person-year follow-up period, 1100 deaths were identified. Men and women were analyzed together as no effect modification by sex was found. After adjusting for multiple potential confounders, the risk of all-cause mortality decreased as the plasma 25(OH)D concentration increased ( P -trend <0.01). Compared with the lowest age-specific quartile of plasma 25(OH)D, the adjusted HRs for mortality for the second, third, and fourth age-specific quartiles were 0.72 (95% CI: 0.57, 0.90), 0.73 (95% CI: 0.58, 0.93), and 0.61 (95% CI: 0.47, 0.81), respectively. The observed associations were broadly consistent across age and other subgroups. Sensitivity analyses generated similar results after excluding participants who died within 2 y of follow-up or after further adjustment for ethnicity and chronic diseases. Conclusions: A higher plasma 25-hydroxyvitamin D concentration was associated with a reduced risk of all-cause mortality among Chinese adults aged ≥80 y. This observed inverse association warrants further investigation in randomized controlled trials testing vitamin D supplementation in this age group.